Comprehensive Test and Evaluation Analysis of Permeable Concrete (PC) Clogging by Using Steel Slag - Cao Yang; Ismail Shah; Wang Jing; Nauman Khan; Li Jing (Advances in Civil Engineering)
In recent decade, researchers have more attention to water resource protection and forward the concept of sponge city construction. PC is becoming more and more popular as a rainwater management tool because of fast climate changes worldwide. In this experiment, PC specimens were prepared with steel slag as aggregate, and the targeted porosity of specimens was 15%, 20%, and 25% respectively, and the ratio of water to cement was 0.38, 0.4, and 0.42. The PC specimens under the 200 mm high head are the most severely blocked; 0.283 m/s high-speed horizontal runoff appears after the rapid plugging stage later in the other two types of speed tests. With time, the plugging effect of the test specimen is almost the same; the clogging degree of the PC sample with the porosity of 25% is more obvious than that of other porosity test specimens. The PC with large porosity is more serious to clogging because the higher seepage velocity will enter the internal tunnel with higher penetration force, which increases the possibility of clogging. Tests have shown that, at different rainwater runoff head heights, the PC specimens under the 200 mm high head are the most severely blocked; 0.283 m/s high-speed horizontal runoff appears after the rapid plugging stage later in the other two types of speed tests but over time. With time, the plugging effect of the test specimen was almost the same; the clogging degree of the permeable concrete sample with the porosity of 25% is more obvious than that of other porosity test specimens. While it is noticed that the compressive strength of the PC after clogging has decreased in the freeze-thaw environment, the destruction process is faster than the unblocked test specimen.